2008
DOI: 10.1007/s00439-008-0554-0
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA1 mutations predispose to pancreatic adenocarcinoma

Abstract: Although the association of germline BRCA2 mutations with pancreatic adenocarcinoma is well established, the role of BRCA1 mutations is less clear. We hypothesized that the loss of heterozygosity at the BRCA1 locus occurs in pancreatic cancers of germline BRCA1 mutation carriers, acting as a "second-hit" event contributing to pancreatic tumorigenesis. Seven germline BRCA1 mutation carriers with pancreatic adenocarcinoma and nine patients with sporadic pancreatic cancer were identified from clinic- and populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…The association between BRCA1 mutations and PC is less widely reported, but the relative risk of PC in BRCA1 mutation carriers is estimated to be twofold higher than in the general population [1][2][3][4][5][6][7][8][9][10][11]. An analysis of PC patients from the Polish population recently showed that there is no relationship between BRCA1 mutation and PC development, while American and Canadian studies concluded that BRCA1 germline mutations likely predispose to the development of PC [5,8,10]. In addition, recent findings in Ashkenazi BC/PC families suggest that the distribution of BRCA1 versus BRCA2 mutations in these families is nearly equal [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…The association between BRCA1 mutations and PC is less widely reported, but the relative risk of PC in BRCA1 mutation carriers is estimated to be twofold higher than in the general population [1][2][3][4][5][6][7][8][9][10][11]. An analysis of PC patients from the Polish population recently showed that there is no relationship between BRCA1 mutation and PC development, while American and Canadian studies concluded that BRCA1 germline mutations likely predispose to the development of PC [5,8,10]. In addition, recent findings in Ashkenazi BC/PC families suggest that the distribution of BRCA1 versus BRCA2 mutations in these families is nearly equal [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Germline BRCA1 mutations only account for a small proportion of familial PDAC, although the risk of developing PDAC in BRCA1 mutation carriers appears to be similar to that of BRCA2 mutation carriers (Ford et al 1994, Thompson et al 2002, Al-Sukhni et al 2008, Vincent et al 2011, Ryan et al 2014, Neuzillet et al 2015. The PALB2 (partner and localizer of BRCA2) protein binds to the BRCA1/2 proteins and ensures nuclear addressing ).…”
Section: Other Gene Mutations Favoring Pdac Developmentmentioning
confidence: 99%
“…The tremendous relevance of an intact homologous recombination-mediated DSB repair machinery is underscored by the observation that patients carrying germline mutations in different homologous recombination genes, such as ATM, BRCA1, BRCA2, and RAD51C display a dramatically elevated risk for the development of neoplastic diseases (22)(23)(24)(25)(26)(27)(28). Furthermore, recurrent somatic proteindamaging mutations or focal deletions of ATM, BRCA1, BRCA2, CHEK2, RAD50, RAD51C, and others have been found in multiple cancer entities (29)(30)(31)(32)(33).…”
Section: Dsb Repair Defects As a Therapeutic Targetmentioning
confidence: 99%